2019
DOI: 10.5812/gct.86579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rs929271 SNP in Leukemia Inhibitory Factor Gene on Recurrent Pregnancy Loss, Placental Location and Fetal Gender

Abstract: Leukemia inhibitory factor (LIF) has an essential role in embryo implantation and placentation. The purpose of this study was to investigate the association of rs929271 SNP on LIF gene with recurrent pregnancy loss (RPL), placental location, and fetal gender in Iranian Azeri women. A total of 300 Azeri women (150 women with at least two recurrent miscarriages and 150 women with at least two healthy deliveries, as the control group) were genotyped for the 3'UTR region T>G SNP on LIF gene (rs929271) by real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…the lowest for placental position of TG versus the TT genotype was posterior location (P = 0.0464). The allele G caused more female embryos than T Allele (Heydarzadeh et al, 2019) as shown in Table 2. .…”
Section: ) (Saftlas Et Al 2003)mentioning
confidence: 94%
“…the lowest for placental position of TG versus the TT genotype was posterior location (P = 0.0464). The allele G caused more female embryos than T Allele (Heydarzadeh et al, 2019) as shown in Table 2. .…”
Section: ) (Saftlas Et Al 2003)mentioning
confidence: 94%